Pastoral Assistance for Adolescent Gadget and Internet Users in the Waldensian Seventh-day Adventist Church - Siang, Jhoni Lagun; Pardosi, Milton T. (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to obtain data regarding Pastoral Assistance for Adolescent Gadget and Internet Users in the Waldensian Seventh-day Adventist Church. The type of research used is literature study. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials (Zed, 2008). Literature study is a required activity in research, especially academic research whose main aim is to develop theoretical aspects as well as aspects of practical benefit. Research results show that to overcome the lack of interest of teenagers in church worship, it is important for churches and pastors to understand the perspectives and needs of teenagers, and to create an inclusive, relevant and empowering environment for them. This can involve creating engaging programs and activities, listening empathetically to their concerns and questions, and building strong relationships between youth and the church community.